2022
DOI: 10.1155/2022/3708547
|View full text |Cite|
|
Sign up to set email alerts
|

Analysis of miRNA Associated with Coronary Artery Calcification

Abstract: Cardiovascular diseases seriously endanger human physical and mental health and life safety, to investigate correlation between miR-let-7b and miR-29b and coronary artery calcification of various patients. At present, real-time fluorescence quantitative PCR (qRT-PCR) was used to detect the expression levels of plasma miR-let-7b and miR-29b in patients with coronary artery calcification and noncoronary artery calcification and to analyze whether the expression levels of miR-let-7b and miR-29b were different bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…CAC is frequently associated with different chronic inflammatory diseases, such as diabetes, chronic kidney disease, and aging, that are widely diffused in developed countries; for this reason, the identification of theranostic markers could be very useful. Yang et al [ 78 ] reported that the under-regulation of miR-29 in serum samples may be considered an important signal of early identification of CAC. In agreement with this study, He et al [ 52 ] concluded that lower plasma levels of miRNA-29b may be used as independent risk factors for the incidence of cardiovascular events (CVEs) and CAC.…”
Section: Resultsmentioning
confidence: 99%
“…CAC is frequently associated with different chronic inflammatory diseases, such as diabetes, chronic kidney disease, and aging, that are widely diffused in developed countries; for this reason, the identification of theranostic markers could be very useful. Yang et al [ 78 ] reported that the under-regulation of miR-29 in serum samples may be considered an important signal of early identification of CAC. In agreement with this study, He et al [ 52 ] concluded that lower plasma levels of miRNA-29b may be used as independent risk factors for the incidence of cardiovascular events (CVEs) and CAC.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, TCG miR-126-3p/5p, -145-5p, and -29b-3p demonstrated a significant distinctive ability to predict the presence of TCFAs (p < 0.05). The miR-29b-3p is also supposed to be involved in the calcification of atherosclerotic plaque [30]. The effect of miR-29b-3p on the endothelial function is presumably realized through tumor necrosis factor receptor 1 (TNF-R1), which counteracts the pro-inflammatory effect of tumor necrosis factor alpha (TNFα) [31].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, miR-29b-3p downregulated VSMC calcification by targeting matrix metalloproteinase 2 (MMP2) and Wnt family member 7B (Wnt7b)/β-catenin signal ( 105 107 ). The expression of miR-29b in the coronary artery calcification group was significantly lower than that in the control group, indicating that decreased miR-29b-3b level may be a coronary artery calcification risk factor ( 108 ). However, it is a paradox that Fang et al .…”
Section: The Flexibility and Versatility Of Mirnas Encapsulated In Ec...mentioning
confidence: 99%